The Influence of Emotional Intelligence on Generation Z Students to Improve Soft Skills - Rivana Deva Siahaan; Annisa Putri Hairani; Putra Ananda Sinaga; Rodeo Dongoran; Dionisius Sihombing; Kevin Pradipta Sitepu (Outline Publisher, 2025)
This is study aims to identify the influence of emotional intelligence on the development of soft skills in generation Z students. The study was conducted with quantitative approach use a correlational survey method, involving 30 students of the Faculty of Economics, State University of Medan as respondents. Data were collected through a Likert-based questionnaire that measures emotional intelligence based on five main dimensions (self-awareness, self-control, motivation, empathy, and social skills) and soft skills (communication, cooperation, leadership, and problem solving). Data analysis was carried out using simple regression tests, ANOVA, and coefficient of determination. The results showed that emotional intelligence did not have a significant effect on improving soft skills, indicated by the F-count (0.000), R-square (0.000), and T-count (0.007) values ​​which were smaller than the T-table. These findings indicate that the development of students' soft skills requires a multidimensional approach that does not only rely on emotional intelligence. This study provides new insights for educational institutions in designing programs to develop skills for generation Z students.